Model test study on the dynamic response of high-speed railway subgrade crossing ground fissure zone - Wang, Zuochen; Huang, Qiangbing; Xie, Qingyu; Xue, Liming; Kang, Xiaosen; Gou, Yuxuan (Frontiers in Earth Science, 2023)
Ground fissure is a typical geohazard widely developed in China, which brings serious geological challenges to the construction and safe operation of the Chinese high-speed railways. However, the dynamic response mechanism of high-speed railway natural subgrade crossing the ground fissure zone is unclear. In this study, a new trainload excitation equipment that can simulate moving train loads was developed. The model test was carried out on the dynamic responses of the natural subgrade of high-speed railway crossing ground fissure zone under moving train loads. The results show that the ground fissure had a great influence on the acceleration response of the subgrade across the ground fissure zone, and the average peak acceleration value of the subgrade in the hanging wall was greater than the footwall. Along the longitudinal direction of the railway, the dynamic earth pressure of the subgrade in the hanging wall was significantly greater than that in the footwall of the ground fissure and is about 2.5 times than that in the footwall, demonstrating a typical hanging wall amplification effect. The displacement amplitude on the subgrade and ground surface in the hanging wall was larger than that in the footwall of ground fissure. The attenuation rate of peak acceleration, dynamic velocity, and displacement in the hanging wall along the depth direction was more evident than that of the footwall of ground fissure.For the natural subgrade of high-speed railway crossing ground fissure zone, the critical influence depth of moving train load was about 12 m below the subgrade surface.